Ion-Neutral Coupling in the Ionospheric Dynamo Region - Measurements, Application and Impact on Ionospheric Variability - Günzkofer, Florian Ludwig; Stober, Gunter; Pokhotelov, Dimitry; Borries, Claudia (2023)
Ionospheric conductivities transverse to the magnetic field lines maximize in the ionospheric dynamo region at about 80 - 150 km altitude. Due to the plasma-neutral interactions, neutral winds contribute to the generation of currents and electric fields in this region. Atmospheric oscillations, e.g. gravity waves and tides, at these altitudes, are therefore important for the variability of the ionosphere. Measurements of atmospheric dynamics at these altitudes are extremely difficult due to the limited number of instruments that cover the dynamo region. Incoherent Scatter Radars (ISRs) can measure basic plasma parameters at dynamo region altitudes and neutral dynamics can be inferred from that due to the coupling of ionosphere and neutral atmosphere. We present measurements of tidal oscillations and atmospheric gravity waves in the thermosphere derived from ISR observations of ionospheric parameters. Both types of waves can be forced either in situ in the thermosphere or propagate upward from the lower and middle atmosphere. In combination with horizontally resolved measurements from the Nordic Meteor Radar Cluster, gravity wave parameters derived from ISR electron density measurements can be applied to infer neutral wind velocities in the thermosphere. We demonstrate this on multiple detections of gravity waves. The coupling of atmospheric waves into the ionospheric plasma strongly depends on the ion-neutral collision frequency. Direct measurement of the ion-neutral collision frequency is only possible with simultaneous measurements using two ISRs with significantly different transmission frequencies. We demonstrate the difference spectrum method which allows us to infer ion-neutral collision frequencies from dual-frequency measurements with the EISCAT UHF and VHF ISRs. Since this method is based on the standard EISCAT analysis software GUISDAP, it is more suited for the general application than previously reported methods.